Ion‐scale structure in Mercury's magnetopause reconnection diffusion region. Issue 12 (20th June 2016) - Gershman, Daniel J.; Dorelli, John C.; DiBraccio, Gina A.; Raines, Jim M.; Slavin, James A.; Poh, Gangkai; Zurbuchen, Thomas H.
Abstract: The strength and time dependence of the electric field in a magnetopause diffusion region relate to the rate of magnetic reconnection between the solar wind and a planetary magnetic field. Here we use 150 ms measurements of energetic electrons from the Mercury Surface, Space Environment, GEochemistry, and Ranging (MESSENGER) spacecraft observed over Mercury's dayside polar cap boundary (PCB) to infer such small‐scale changes in magnetic topology and reconnection rates. We provide the first direct measurement of open magnetic topology in flux transfer events at Mercury, structures thought to account for a significant portion of the open magnetic flux transport throughout the magnetosphere. In addition, variations in PCB latitude likely correspond to intermittent bursts of 0.3–3 mV/m reconnection electric fields separated by 5–10 s, resulting in average and peak normalized dayside reconnection rates of 0.02 and 0.2, respectively. These data demonstrate that structure in the magnetopause diffusion region at Mercury occurs at the smallest ion scales relevant to reconnection physics. Key Points: Energetic electrons at Mercury map magnetic topology at 150 ms First direct observation of flux transfer event open‐field topology at Mercury Modulations of the reconnection rate at Mercury occur at ion kinetic scales